2010
DOI: 10.1002/adem.201080070
|View full text |Cite
|
Sign up to set email alerts
|

XPS Studies of Magnesium Surfaces after Exposure to Dulbecco's Modified Eagle Medium, Hank's Buffered Salt Solution, and Simulated Body Fluid

Abstract: Magnesium‐based biomaterials are gaining increasing interest, while in vitro corrosion tests are not standardized yet. Moreover, the effects of different corrosion media on the corrosion products are still not fully understood. To compare and evaluate the three main corrosion media applied in most in vitro studies, an XPS investigation of magnesium surfaces was carried out after exposure of the specimens to Dulbecco's modified eagle medium (DMEM), Hank's buffered salt solution (HBSS), and simulated body fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…It is not yet clear whether proteins adhere to degrading magnesium in the same way as they do to permanent materials . Remnants of proteins were hardly found in the corrosion layer (Tie et al, 2010). The presence of silver decreased the corrosion process, while bringing no additional toxicity, which provided a better environment for cell adhesion than pure magnesium.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is not yet clear whether proteins adhere to degrading magnesium in the same way as they do to permanent materials . Remnants of proteins were hardly found in the corrosion layer (Tie et al, 2010). The presence of silver decreased the corrosion process, while bringing no additional toxicity, which provided a better environment for cell adhesion than pure magnesium.…”
Section: Discussionmentioning
confidence: 94%
“…To be as close to in vitro conditions as possible, cell culture medium DMEM (supplemented with proteins) was selected (Mueller et al, 2010;Tie et al, 2010). Previous studies reported that the presence of proteins results in a different corrosion behaviour (Williams and Williams, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…7). A possible cross reaction could be NaHCO 3  Na + + HCO 3 - [74], which is involved in the buffering system under the influence of CO 2 and interferes with the equilibrium of NaCl dissociation and consequently the effects of Cl -on Mg corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…5C) was carried out to identify distinct Mg binding energies and compounds. The Mg 2p spectra stretched out from 47.0 eV to 52.8 eV [41]. The broadening of the peak was deconvoluted and fitted with Mg(OH) 2 at 49.4 eV, MgO at 50.2 eV and Mg-PO 4 at 50.8 [42].…”
Section: Clinical Observations and In Vivo Degradation Processmentioning
confidence: 99%